AuAg/ZnO nanocatalyst for CO2 valorization and H2 and CO electrochemical production. Issue 39 (July 2020) - Sarno, Maria; Ponticorvo, Eleonora; Piotto, Stefano; Nardiello, Anna Maria; De Pasquale, Salvatore; Funicello, Nicola
Highlights: Direct electrochemical conversion of carbon dioxide. H2O and CO2, through syngas mediated productions, vs. chemicals, pharmaceuticals or biofuels. Active sites on AuAg/ZnO functionalized nanocatalyst. 94.7 % of Faradic efficiency at 0.4 V. Electronic properties of Ag/Au nanoalloy and AuAg/ZnO heterojunction. Abstract: A controllable composition and morphology AuAg/ZnO catalyst, prepared by an easily scalable method, was, for the first time, explored for the electrocatalytic reduction of CO2 . It was found that the composition of the bimetallic alloy contributes to the overall CO2 reduction performance. In particular, as also demonstrated by density functional theory calculations, CO production increases, decreasing the Au content in the catalyst alloy. The experimental investigation reveals that the products are H2 and CO, which production rate increases in the presence of ZnO, up to a Faradic efficiency of 94.7 % at 0.4 V. On the other hand, controlling the oleic acid covering it is possible to modulate the surface properties allowing to obtain, at 0.6 V, H2 /CO ratios equal to 1.1 and 1.9 for nanocatalysts thermally treated for 2 and 5 h, respectively.